Testing Becker’s Theory of Positive Assortative Matching - Siow, Aloysius (Journal of Labor Economics, 2015)
In a stochastic Becker marriage model (Choo and Siow), supermodularity of the match output function implies stochastic positive assortative matching (PAM): the equilibrium marriage matching distribution has all positive local log odds ratios or is totally positive of order 2 (TP2). The Choo-Siow model rationalizes the practice of studying PAM independent of population vectors and marriage rates and conditional on other spousal characteristics. Using white married couples in their 30s from the 2000 US Census, spousal educational matching generally obeyed TP2. Between 1970 and 2000, there was no general increase in PAM. There was increased homogamy in spousal education matching.